A waste-free congestion control scheme for dual bus high-speed networks. - Huang, Nen-Fu
In a high speed backbone network, each of the nodes in the backbone may act as a router/gateway which connects several low speed LANs. Typically, a router/gateway occurs congestion when the traffic from the backbone network can not be serviced by the connected LANs. Recently, since the existence of high speed LANs becomes possible, a router/gateway may also occur congestion when the traffic from the connected LANs can not be serviced by the backbone network. In this paper, a waste free congestion control MAC protocol for dual bus high speed networks is proposed to release such congestion. In this protocol, a heavy loaded node obtains a faster transmission rate to send the packets so that the congestion can be prevented efficiently. Meanwhile, each of the uncongested nodes slows down its transmission rate and stores the new incoming messages into its buffer. We show that the proposed protocol is waste free and hence the throughput of the network is maximized. A simple and efficient priority mechanism is also introduced for the proposed protocol to support multi-priority traffic in networks. The efficiency of the proposed protocol is compared to the well known protocols for the dual bus networks, such as the DQDB with BBM and the BA-FDQ. Simulation results show that the proposed protocol is more efficient than the other well-known schemes in terms of message queueing delay, message loss rate and network throughput.
Keywords: Congestion control; DQDB; Dual-bus.; MAC protocol; Waste free